Statistical Evaluation of the Material-Source Effect on the Ductility and Elastic Recovery (ER) of Plant-Mix Extracted Asphalt-Binders - Lubinda F. Walubita; Gilberto Martinez-Arguelles; Harshavardhan R. Chunduri; Jose G. Gonzalez Hernandez; Luis Fuentes (Advances in Civil Engineering)
This study was conducted to quantitatively and statistically evaluate the effects of material source on the ductility of asphalt-binders, measured in terms of the elastic recovery (ER) property. The ER data used in the study were excerpted from the Texas flexible pavements and overlays database, namely, the Texas Data Storage System (DSS), covering plant-mix extracted PG XX-22 asphalt-binders (i.e., rolling thin film oven (RTFO) residues) from 20 different sources and measured using the Ductilometer test at 10°C. The findings of the study indicated that material source has an impact on the ER property of asphalt-binders. Statistically significant differences were observed among some sources and suppliers that reported the same low-temperature asphalt-binder type/grade (i.e., PG XX-22). Overall, the study contributes to enriching the literature on the material-source effects on asphalt-binders’ ER properties, consistency, variability, and data quality. In particular, the study highlights the sensitivity nature of the asphalt-binder ER parameter to material-source effects.